Blow up the humanities - Miller, Toby, 1958- (Temple University Press, 2012)
"A short, sharp, and provocative book, Blow Up the Humanities has esteemed scholar Toby Miller declaring that there are two humanities in the United States. One is the venerable, powerful humanities of private universities; the other is the humanities of state schools, which focus mainly on job prospects. There is a class division between the two--both in terms of faculty research and student background--and it must end. Miller critically lays waste to the system. He examines scholarly publishing as well as media and cultural studies to show how to restructure the humanities by studying popular cultural phenomena, like video games. Miller ultimately insists that these two humanities must merge in order to survive and succeed in producing an aware and concerned citizenry"--Provided by publisher.